Implementasi Pendekatan Kontekstual dalam Pembelajaran PAI untuk Meningkatkan Pemahaman dan Minat Belajar Siswa di SMP NU Sunan Kalijaga Adiwerna - Qotrunnada, Nabila; Indianto S, Dimas (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to apply a contextual approach in Islamic Religious Education learning to improve students' understanding and interest in learning at SMP NU Sunan Kalijaga Adiwerna. The use of a contextual approach in learning at school is the right step to help students relate Islamic teachings to students' daily lives in the real world. A contextual approach can also improve students' understanding and interest in learning because the learning materials taught by teachers are very relevant to life in the real world. This study uses a qualitative approach with a descriptive field research type. The research was conducted through observation, interview, and documentation activities. The location of the research was at SMP NU Sunan Kalijaga Adiwerna with research subjects of two Islamic Religious Education teachers and grade IX students. The results of this study indicate that the application of a contextual approach in Islamic Religious Education learning to improve students' understanding and interest in learning at SMP NU Sunan Kalijaga Adiwerna applies seven learning components through three stages, namely planning, implementation, and evaluation. The seven components are constructivism, inquiry, asking, learning community, modeling, reflection, and authentic assessment